Life histories of the Dobe!Kung : food, fatness, and well-being over the life span - Howell, Nancy (Origins of human behavior and culture ;, 2010)
Life Histories of the Dobe!Kung re-examines an important anthropological data set collected by Nancy Howell and colleagues for the Dobe!Kung, the well-known "Bushmen" of the Kalahari Desert. Using life history analysis, Howell reinterprets this rich material to address the question of how these hunter-gatherers maintain their notably good health from childhood through old age in the Kalahari's harsh environment. She divides the population into life history stages that correlate with estimated chronological ages and demonstrates how and why they survive, even thrive, on a modest allotment of.